X MARCKS the spot: myristoylated alanine-rich C kinase substrate in neuronal function and disease - Brudvig, Jon J.; Weimer, Jill M. (Frontiers in Cellular Neuroscience, 2015)
Intracellular protein-protein interactions are dynamic processes requiring tightly regulated spatial and temporal checkpoints. But how are these spatial and temporal cues integrated to produce highly specific molecular response patterns? A helpful analogy to this process is that of a cellular map, one based on the fleeting localization and activity of various “guide” proteins that direct a wide array of interactions between key molecules. One such “guide” protein, Myristoylated alanine-rich substrate of protein kinase C (MARCKS) has recently emerged as an important component of this cellular map, governing a wide variety of protein interactions in every cell type within the brain. In addition to its well-documented interactions with the actin cytoskeleton, MARCKS has been found to interact with a number of other proteins involved in processes ranging from intracellular signaling to process outgrowth. Here we will explore these diverse interactions and their role in an array of brain-specific functions that have important implications for many neurological conditions.